Role of myoglobin in regulating respiration during muscle contraction - Kazumi Masuda; Tatsuya Yamada; Rie Ishizawa; Hisashi Takakura (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Oxygen (O2) transport from air to mitochondria depends on both the mechanisms of convection and diffusion. In the final step of the O2 cascade, from the capillary to myocyte, O2 is transported into cells via diffusion according to the potential differences in PO2 across plasma membranes. Myoglobin (Mb), an important cellular O2 binding protein that is expressed in skeletal and cardiac muscle cells, has been known as an O2 store or O2 transporter for more than half a century. However during the last decade, Mb functions have been re-assessed as a result of further knowledge gained from Mb-deficient mice that suggest other functions beyond its function as an O2 store. At first glance, Mb-deficient mice do not show any superficial physiological deficits. However, homeostatic mechanisms, including increased capillary density that tends to steepen the PO2 gradient to the mitochondria, effectively shorten the diffusion path for O2. Recent research demonstrated that Mb is releasing its binding O2 at onset of muscle contraction to manipulate intracellular O2 content. The O2 gradient Mb substantially contributes to nitric oxide homeostasis, and could interact with substrates such as fatty acid. This recent experimental evidence will help us to refine our understanding of Mb physiological function and establish a basis for further research.